An Old Problem in Draft of the New Code of the Russian Federation on Administrative Offences - Aleksei A. Grishkovets (Сибирское юридическое обозрение, 2020)
The article analyzes the provisions of the draft of the Code of the Russian Federation on Administrative Offenses, developed on the basis of the Concept approved in 2019 by the Russian Government. Attention is drawn to the fact that the Concept, for the first time in domestic practice, contains a provision stating that improving the institution of administrative responsibility will require work to transform it from a predominantly punitive-fiscal instrument into the institution of sentencing, subject to differentiated application taking into account the risk-based approach. Based on the analysis of particular compositions of the draft of the Code of Administrative Offenses, it has been concluded that the punitive-fiscal orientation in it remains. Suggestions have been made on possible ways to overcome this. Administrative penalties should only provide general and specific prevention. The economy of administrative repression should become an element of the administrative policy of the executive branch. After the entry into force of the new Code of the Russian Federation on Administrative Offenses, it has been proposed to conduct annual monitoring of its application, which will make it possible to identify the compositions that bring the greatest income to the budget. The problem of the existence of a profitable business on administrative responsibility is outlined. Attempts to introduce public-private partnership related to the provision of police assistance are assessed negatively. Based on Russian realities, it can be assumed that in practice this will lead to abuse by police officers and, as a result, to violation of human and civil rights and freedoms. Only in the future, the Russian police should gradually transform from a purely security structure focused on the use of state coercion measures into a structure that is largely service, providing citizens with specific services, in particular, providing them with police assistance when necessary. The idea is supported to recognize the “right to error” and “the right to forgiveness” for an administrative offender. It is proposed to implement it by expanding the possibilities of applying a warning as an alternative to such a punishment as an administrative fine, as well as by expanding the list of possible grounds for exemption from administrative liability. It is concluded that the adoption of the draft of the Code of the Russian Federation on Administrative Offenses does not look obvious.